Acknowledge Center Model (BCCT) for Learning in Early Childhood Education and its Application to Independent Curriculum - Maimunah Maimunah (CV. Ridwan Publisher, 2023)
This article aims to discuss the BCCT learning model or often known as the Center Method which discusses the history of the beginning of the presence of this learning model, its advantages and disadvantages, its characteristics, principles and purposes and objectives of the presence of this learning model. Hopefully, with this article, it can become a reference material for ECCE educators because they are the most competent parties and have an important role in the implementation of Early Childhood Education. This article uses descriptive studies by collecting theories from various relevant sources, using literature studies, namely collecting various information from books, journals and related articles. Then the results of this study are directed at the benefits with an independent curriculum related to the identity of the Pancasila Student Profile.